Optimized Driver Placement for Array-Driven Flat-Panel Loudspeakers - ANDERSON, David A.; HEILEMANN, Michael C.; BOCKO, Mark F. (Archives of Acoustics, 2017)
The recently demonstrated ‘modal crossover network’ method for flat panel loudspeaker tuning employs an array of force drivers to selectively excite one or more panel bending modes from a spectrum of panel bending modes. A regularly spaced grid of drivers is a logical configuration for a two-dimensional driver array, and although this can be effective for exciting multiple panel modes it will not necessarily exhibit strong coupling to all of the modes within a given band of frequencies. In this paper a method is described to find optimal force driver array layouts to enable control of all the panel bending modes within a given frequency band. The optimization is carried out both for dynamic force actuators, treated as point forces, and for piezoelectric patch actuators. The optimized array layouts achieve similar maximum mode coupling efficiencies in comparison with regularly spaced driver arrays; however, in the optimized arrays all of the modes within a specified frequency band may be independently addressed, which is important for achieving a desired loudspeaker frequency response. Experiments on flat panel loudspeakers with optimized force actuator array layouts show that each of the panel modes within a selected frequency band may be addressed independently and that the inter-modal crosstalk is typically −30 dB or less with non-ideal drivers.